Jury Pool Underrepresentation in the Modern Era: Evidence from Federal Courts. Issue 2 (28th March 2018) - Rose, Mary R.; Casarez, Raul S.; Gutierrez, Carmen M.
Abstract : Despite a constitutional mandate that jury pools in the United States be representative of their communities, almost no datasets exist that can describe typical levels and patterns of jury representation. We present data from federal courts on the composition of jury pools in 52 areas, representing 764 counties. We also compare current composition estimates to those available 20 years ago from published sources. Results show that, by far, some amount of underrepresentation in jury pools is the norm, and levels of attrition fail all but one proposed method for calculating and defining "not fair and reasonable" amounts of underrepresentation. On average, expected losses range between one and three members of each minority group from jury venires of 40 to 60 people. We find no evidence that the impact of attrition on Latino communities is greater than on African‐American communities and, unlike Latinos, no indicators of African‐American representation levels show improvement over time. We discuss the challenges of addressing racial/ethnic attrition in jury pools, which is evident but, given the repeated small‐group sampling of venires, may be small in effect in any single case.